FAP Promotes Immunosuppression by Cancer-Associated Fibroblasts in the Tumor Microenvironment via STAT3–CCL2 Signaling - Yang, Xuguang; Lin, Yuli; Shi, Yinghong; Li, Bingji; Liu, Weiren; Yin, Wei; Dang, Yongjun; Chu, Yiwei; Fan, Jia; He, Rui (Cancer research (Chicago, Ill.), 2016)
Cancer-associated fibroblasts (CAF) are components of the tumor microenvironment whose contributions to malignant progression are not fully understood. Here, we show that the fibroblast activation protein (FAP) triggers induction of a CAF subset with an inflammatory phenotype directed by STAT3 activation and inflammation-associated expression signature marked by CCL2 upregulation. Enforcing FAP expression in normal fibroblasts was sufficient to endow them with an inflammatory phenotype similar to FAP+CAFs. We identified FAP as a persistent activator of fibroblastic STAT3 through a uPAR-dependent FAK–Src–JAK2 signaling pathway. In a murine liver tumor model, we found that FAP+CAFs were a major source of CCL2 and that fibroblastic STAT3–CCL2 signaling in this setting promoted tumor growth by enhancing recruitment of myeloid-derived suppressor cells (MDSC). The CCL2 receptor CCR2 was expressed on circulating MDSCs in tumor-bearing subjects and FAP+CAF-mediated tumor promotion and MDSC recruitment was abrogated in Ccr2-deficient mice. Clinically, we observed a positive correlation between stromal expression of FAP, p-STAT3, and CCL2 in human intrahepatic cholangiocarcinoma, a highly aggressive liver cancer with dense desmoplastic stroma, where elevated levels of stromal FAP predicted a poor survival outcome. Taken together, our results showed how FAP–STAT3–CCL2 signaling in CAFs was sufficient to program an inflammatory component of the tumor microenvironment, which may have particular significance in desmoplasia-associated cancers. Cancer Res; 76(14); 4124–35. ©2016 AACR.